PSYCHOLOGISM IN THE STORIES OF T.SYDYKBEKOV (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article is devoted to the work of the writer T. Sydykbekov “Kok Serek”, “Kek”and others, written in the 80s. ideological and thematic analysis of stories. An analysis of the disclosure of the inner world of the heroes, the author’s presentation at a high level, that the prosewriter especially managed to reveal the images of the heroes through the prism of circumstancesand life’s difficulties. The processes of overcoming them and learning lessons most fully reveal theinner world and psychology of the characters, forcing the reader to empathize with the characters.The general line of T. Sydykbekov’s stories is moral values accepted in society, the need to makedifficult decisions, questions of the formation of the personality of the main characters.
Keywords: story, hero, nature, wolf, psychology, idea, character, writer